2019
DOI: 10.18632/oncotarget.26945
|View full text |Cite
|
Sign up to set email alerts
|

AGR2, a unique tumor-associated antigen, is a promising candidate for antibody targeting

Abstract: Anterior gradient 2 (AGR2), a protein disulfide isomerase, shows two subcellular localizations: intracellular (iAGR2) and extracellular (eAGR2). In healthy cells that express AGR2, the predominant form is iAGR2, which resides in the endoplasmic reticulum. In contrast, cancer cells secrete and express eAGR2 on the cell surface. We wanted to test if AGR2 is a cancer-specific tumor-associated antigen. We utilized two AGR2 antibodies, P3A5 and P1G4, for in vivo tumor localization and tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…functions are under development [51,52], but agents that block the essential role of AGR2 in the folding of client proteins are not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…functions are under development [51,52], but agents that block the essential role of AGR2 in the folding of client proteins are not available.…”
Section: Discussionmentioning
confidence: 99%
“…However, AGR2 may also be secreted and promote tumor angiogenesis [49, 50] and act on cell surface receptors [51]. Monoclonal antibodies designed to block extracellular AGR2 functions are under development [51, 52], but agents that block the essential role of AGR2 in the folding of client proteins are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Each cDNA contained a Kozak box. Plasmids of chimeric P1G4 hIgG1, hIgG2, hIgG4; P3A5 hIgG1, hIgG2, hIgG4 were generated [22]. The different Cγ plasmids could be distinguished by Sac II and Eco RI digestion.…”
Section: Chimeric Human:mouse Agr2 Antibodiesmentioning
confidence: 99%
“…Mouse antibodies, besides being immunogenic in human, do not interact efficiently with human immune system components. To overcome these drawbacks, we have replaced the constant domains of AGR2 antibodies by the analogous human constant domains via recombinant DNA technology [21], generating human:mouse chimeric hIgG1, hIgG2, hIgG4 for both P1G4 and P3A5 for potential therapeutic development [22].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study that showed such promising result of antibody-based therapy targeting AGR2, suggesting that this molecule is an important target in cancer development. Another rather exciting finding is the production of two humanized monoclonal anti-AGR2 antibodies, when incubated with human blood, resulting in cell lysis of prostate cancer cells containing eAGR2 [ 113 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%